Effect of Natural Ilmenite on the Solid Biomass Conversion of Inhomogeneous Fuels in Small-Scale Bubbling Fluidized Beds - Schneider, Tanja; Müller, Dominik; Karl, Jürgen (Energies, 2022)
The application of oxygen carriers as alternative bed material in fluidized bed combustion originates from chemical lopping processes. They serve as oxygen transport agents undergoing consecutive redox cycles. Thereby, oxygen carriers can provide surplus oxygen in oxygen-lean areas of fluidized bed combustion processes. In turn, re-oxidation takes place in oxygen-rich reactor parts. A more homogeneous combustion and reduced CO emissions follow during steady-state operation. However, especially regarding solid biomass conversion, inhomogeneous fuel qualities result in transient combustion conditions. Therefore, this research deals with the influence of the oxygen carrier ilmenite on solid biomass conversion. Separated batch experiments with methane (volatile), char and wood pellets took place in a laboratory bubbling fluidized bed reactor. They reveal that ilmenite enhances the in-bed CO2 yield by up to 63% during methane combustion. Batch char experiments confirm that solid–solid reactions with ilmenite are negligible. However, heterogeneous gas–solid reactions reduce the O2 partial pressure and limit the char conversion rate. The batch wood pellet experiments show that the ilmenite oxygen buffering effect is mitigated due to high local oxygen demand around the pellets and limited pellet distribution in the bed. Finally, the continuous operation in a 100 kWth BFB with inhomogeneous fuel input indicates a higher in-bed fuel conversion and confirms lower CO emissions and less fluctuation in the flue gas during inhomogeneous fuel supply.<br
Keywords: ilmenite; oxygen carrier; bubbling fluidized bed; oxygen carrier aided combustion; biomass